Cobalt(ii)/nickel(ii) separation from sulfate media by solvent extraction with an undiluted quaternary phosphonium ionic liquid. Issue 57 (19th July 2017) - Onghena, Bieke; Valgaeren, Stijn; Vander Hoogerstraete, Tom; Binnemans, Koen
Abstract : Co(ii ) is separated from Ni(ii ) in sulfate media by extraction with the ionic liquid Cyphos IL 101 in its chloride and thiocyanate form. Abstract : Leaching of cobalt and nickel from ores, urban waste and industrial residues is in general performed by sulfuric acid rather than hydrochloric acid, because sulfuric acid is cheaper and much less corrosive than hydrochloric acid. The choice of the acidic lixiviant has a large influence on the down-stream separation of Co and Ni, since the anion in the leachate determines the choice of solvent extraction system that can be applied. Co/Ni separations from sulfate media are traditionally performed by acidic extractants. In this paper, the extraction of Co(ii ) from sulfate media and its separation from Ni(ii ) is investigated using the quaternary phosphonium ionic liquid trihexyl(tetradecyl)phosphonium chloride (Cyphos IL 101, [C101][Cl]). Several extraction parameters have been optimized: acid concentration, salt concentration, time, temperature and the initial metal concentration in the aqueous feed solution. Furthermore, the extraction mechanism was investigated. The separation factors of Co(ii )/Ni(ii ) are very high, in the order of 10 5 . Stripping of the extracted Co(ii ) ions from the loaded ionic liquid phase was achieved by mixing with water. The ionic liquid phase was afterwards regenerated by washing with a CaCl2 solution. The extraction of Co(ii ) and Ni(ii ) with [C101][Cl] was compared to the extraction with the thiocyanate form of Cyphos IL 101, [C101][SCN]. It was found that extraction of Co(ii ) with [C101][SCN] occurred according to a split-anion mechanism, whereas a regular anion-exchange mechanism was observed for [C101][Cl].